The Role of Nutri(epi)genomics in Achieving the Body's Full Potential in Physical Activity - Irene Petracci; Rosita Gabbianelli; Laura Bordoni (MDPI AG, 2020)
Physical activity represents a powerful tool to achieve optimal health. The overall activation of several molecular pathways is associated with many beneficial effects, mainly converging towards a reduced systemic inflammation. Not surprisingly, regular activity can contribute to lowering the "epigenetic age", acting as a modulator of risk toward several diseases and enhancing longevity. Behind this, there are complex molecular mechanisms induced by exercise, which modulate gene expression, also through epigenetic modifications. The exercise-induced epigenetic imprint can be transient or permanent and contributes to the muscle memory, which allows the skeletal muscle adaptation to environmental stimuli previously encountered. Nutrition, through key macro- and micronutrients with antioxidant properties, can play an important role in supporting skeletal muscle trophism and those molecular pathways triggering the beneficial effects of physical activity. Nutrients and antioxidant food components, reversibly altering the epigenetic imprint, have a big impact on the phenotype. This assigns a role of primary importance to nutri(epi)genomics, not only in optimizing physical performance, but also in promoting long term health. The crosstalk between physical activity and nutrition represents a major environmental pressure able to shape human genotypes and phenotypes, thus, choosing the right combination of lifestyle factors ensures health and longevity.